First-principles understanding of durable titanium nitride (TiN) electrocatalyst supports - Kwon, Jeong An; Kim, Min-Su; Shin, Dong Yun; Kim, Jin Young; Lim, Dong-Hee (Journal of industrial and engineering chemistry (Seoul, Korea), 2017)
[Display omitted] Transition metal nitrides possessing superior electrical conductivity and outstanding oxidation and corrosion resistance have been described as good substitutes for carbon support materials which are vulnerable during proton exchange membrane fuel cell (PEMFC) operation due to corrosion and poor life cycles. A closer theoretical inspection of the stability and electronic properties of titanium nitride-supported Pt in comparison with carbon-supported Pt (using graphite and graphene) has been conducted using density functional theory calculations. A single Pt atom adsorbed more strongly to the TiN surface than to both graphite and graphene, causing a larger degree of charge transfer between Pt and TiN.